Total hip arthroplasty compared to bipolar and unipolar hemiarthroplasty for displaced hip fractures in the elderly: a Bayesian network meta-analysis - Migliorini, Filippo; Maffulli, Nicola; Trivellas, Mira; Eschweiler, Jörg; Hildebrand, Frank; Betsch, Marcel (European journal of trauma and emergency surgery, 2022)
Displaced femoral neck fractures (FNF) usually require surgical treatment with either a total hip arthroplasty (THA), unipolar hemiarthroplasty (U-HHA), or bipolar hemiarthroplasty (B-HHA). However, there is still controversy regarding the optimal implant. This network meta-analysis compared the outcomes and complication rates of THA versus B-HHA and versus U-HHA in elderly patients with FNF.
Gesehen am 24.10.2023